Retroviral integration: Site matters: Mechanisms and consequences of retroviral integration site selection - Demeulemeester, Jonas; De Rijck, Jan; Gijsbers, Rik; Debyser, Zeger (BioEssays, 2015)
Here, we review genomic target site selection during retroviral integration as a multistep process in which specific biases are introduced at each level. The first asymmetries are introduced when the virus takes a specific route into the nucleus. Next, by co‐opting distinct host cofactors, the integration machinery is guided to particular chromatin contexts. As the viral integrase captures a local target nucleosome, specific contacts introduce fine‐grained biases in the integration site distribution. In vivo, the established population of proviruses is subject to both positive and negative selection, thereby continuously reshaping the integration site distribution. By affecting stochastic proviral expression as well as the mutagenic potential of the virus, integration site choice may be an inherent part of the evolutionary strategies used by different retroviruses to maximise reproductive success.